PROSPECTS FOR ENHANCING INCLUSIVE ECONOMIC ACTIVITY THROUGH MODERN TECHNOLOGIES (American Journal of Business Management, Economics and Banking, 2025)
This article discusses the role and prospects of modern technologies in enhancing the economic activity of visually impaired individuals. In today’s digital era, technologies are considered a key tool for increasing production capacity, improving efficiency, and optimizing time and costs. For visually impaired entrepreneurs, mobile applications, online platforms, cloud technologies, artificial intelligence, and big data are examined as effective approaches to overcoming barriers to economic participation. The article also highlights the importance of technologies in information security, employee productivity, and monitoring economic processes. Furthermore, measures aimed at expanding the economic and social opportunities of visually impaired people, including reforms being implemented in the Republic of Uzbekistan, are analyzed.